Measuring nonlocal coherence with weak-field homodyne detection - Bartley, T; Donati, G; Jin, X; Datta, A; Barbieri, M; Walmsley, I (IEEE, 2013)
A foundation of quantum mechanics is that quantum objects can exhibit both particle-like and wave-like behaviour. Uncovering particular behaviour depends largely on the type of detector used. In an optical setting, photon counting and homodyne detection are typically used to expose particle and wave phenomena, respectively. Recently, weak-field homodyne detection was demonstrated [1], whereby photonic states are interfered with a coherent phase reference of very low mean photon number before being counted. Such a hybrid detection scheme bridges the gap between the particle and wave, or discrete and continuous, description of photons. © 2013 IEEE.